Past-future preferences for hedonic goods and the utility of experiential memories. (17th November 2022) - Lee, Ruth; Shardlow, Jack; O'Connor, Patrick A.; Hotson, Lesley; Hotson, Rebecca; Hoerl, Christoph; McCormack, Teresa
ABSTRACT: Recent studies have suggested that while both adults and children hold past-future hedonic preferences – preferring painful experiences to be in the past and pleasurable experiences to lie in the future – these preferences are abandoned when the quantity of pain or pleasure under consideration is greater in the past than in the future. We examined whether such preferences might be affected by the utility people assign to experiential memories, since the recollection of events can itself be pleasurable or aversive, and we examined the developmental trajectory of the value that people assign to experiential memories of past painful experiences. Using a task in which we manipulated hypothetical memory loss in a series of brief vignettes, we found that for some adults, but not for children, the disutility attached to the recollection of painful past events outweighed the disutility of living through future painful events. Between middle childhood and adulthood, experiential memory appears to assume a more important role in determining the value that people assign to past experiences and in mitigating bias toward the future.